Unconscious Memory in Acquiring New Vocabulary Using Flashcards - Podoliak, Mykhailo (Lesya Ukrainka Volyn National University, 2021)
Most people tend to memorize different things unconsciously, without even taking notice of this process. However, it comprises a vital and effective function of the human mind that requires little effort. Following this perspective, the article aims to analyze the possibility of applying this function in the language learning process, particularly in facilitating the process of memorizing new foreign words. The experiment was conducted to prove the effectiveness of the proposed method and consisted of two phases. First, three focus groups of students were to observe the flashcards alongside the translation of words for the time period of 16 weeks, unconsciously memorizing them. Then, there were two control tests to determine the effectiveness of such a learning method. The present paper also relies on the articles and research activities of numerous scholars, e.g. Standing (1973), Urgolites (2013), Nikolic (2007), Brady, Konkle (2011), Schurgin & Cunningham (2018), showcasing the effectiveness of visual memory in retaining the information for a longer period of time. These studies emphasized the associations that people make while memorizing different things. Our research posits that color flashcards with the translation of words facilitate the process of creating associations among students, ensuring high results of their memory performance. Foreign language teachers can hence use the research results to facilitate learning new words by students.
Keywords: memory; language learning; vocabulary memorizing; long-term memory; flashcards